Economic preferences and compliance in the social stress test of the Corona crisis - Stephan Müller; Holger A. Rau (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
We test in a survey the impact of economic preferences on compliance and perception during the Corona pandemic. Results show that economic preferences crucially impact citizens' compliance to policies fighting the crisis. Risk tolerance negatively a↵ects citizens' avoidance of crowds, whereas patience helps to do so and to stay home. Present-biased subjects engage in panic buying. Risk tolerance is negatively related with the Corona threat and trust positively resonates with positive media perception. Exploiting data from before the crisis allows us to infer causality and to deduce valuable insights for crisis management by identifying target groups or regions for the allocation of scare medical or surveillance resources.
Keywords: C91; D81; H12; H41; 330; Compliance; Covid-19; Experiment; Preferences; Social Responsibility